Deskripsi Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Matematika Materi Perbandingan Ditinjau Dari Gaya Belajar Siswa - Sitti Hartinah; Asdar; Djadir (Issues in Mathematics Education (IMED), 2019)
This study aims to describe the errors made by students in mathematics word problem of proportion topic based on Newmans’ criteria in term of student learning styles. The data collection techniques used are learning styles questionnaire, diagnostic tests and interviews then through three stages of data analysis that are data condensation, presentation, and conclusion. The result of the research showed that the indicator of the direct proportion errors made by (1) subject of visual learning style is encoding errors, (2) subject of auditory learning style are reading errors, comprehension errors, transformation errors, process skill errors and encoding errors, and (3) subject of kinesthetic learning style are comprehension errors, transformation errors, process skill errors and encoding errors. In addition the indicator of the inverse proportion errors made by (1) subject of visual learning style are transformation errors, process skill errors and encoding errors (2) subject of auditory learning style are transformation errors, process skill errors and encoding errors, and (3) subject of kinesthetic learning style are transformation errors, process skill errors and encoding errors.